Changes in SOD and NF-κB Levels in Substantia Nigra and the Intestine through Oxidative Stress Effects in a Wistar Rat Model of Ozone Pollution - Selva Rivas-Arancibia; Erika Rodríguez-Martínez; Marlen Valdés-Fuentes; Alfredo Miranda-Martínez; Eduardo Hernández-Orozco; Citlali Reséndiz-Ramos (MDPI AG, 2024)
This work aimed to elucidate how O3 pollution causes a loss of regulation in the immune response in both the brain and the intestine. In this work, we studied the effect of exposing rats to low doses of O3 based on the association between the antioxidant response of superoxide dismutase (SOD) levels and the nuclear factor kappa light chains of activated B cells (NFκB) as markers of inflammation. Method: Seventy-two Wistar rats were used, divided into six groups that received the following treatments: Control and 7, 15, 30, 60, and 90 days of O3. After treatment, tissues were extracted and processed using Western blotting, biochemical, and immunohistochemical techniques. The results indicated an increase in 4-hydroxynonenal (4HNE) and Cu/Zn-SOD and a decrease in Mn-SOD, and SOD activity in the substantia nigra, jejunum, and colon decreased. Furthermore, the translocation of NFκB to the nucleus increased in the different organs studied. In conclusion, repeated exposure to O3 alters the regulation of the antioxidant and inflammatory response in the substantia nigra and the intestine. This indicates that these factors are critical in the loss of regulation in the inflammatory response; they respond to ozone pollution, which can occur in chronic degenerative diseases.